2020
DOI: 10.1186/s13071-020-3906-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a gp60-subtyping method for Cryptosporidium felis

Abstract: Background: Feline cryptosporidiosis is an increasing problem, especially in catteries. In humans, close contact with cats could be a potential source of infection although the risk of contracting cryptosporidiosis caused by Cryptosporidium felis is considered to be relatively low. Sequencing of the 60-kDa glycoprotein gene is a commonly used tool for investigation of the genetic diversity and transmission dynamics of Cryptosporidium species. However, until now the sequence of gp60 from C. felis has not been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 24 publications
(33 reference statements)
3
59
1
Order By: Relevance
“…In the maximum likelihood tree, the 44 DNA sequences formed four distinct clusters as expected, with 99-100% bootstrap support (Figure 1). Three of the four clusters were found in the previous study [10], while one cluster seen in the previous study, B, was absent from the present study. In accordance with the established nomenclature system for Cryptosporidium subtype families [11], the four clusters found in the present study were named as XIXa, XIXc, XIXd and XIXe (newly identified in the present study) subtype families, while the previous Cluster B was named as XIXb subtype family.…”
Section: Phylogenetic Relationship Among C Felis Subtypescontrasting
confidence: 69%
See 2 more Smart Citations
“…In the maximum likelihood tree, the 44 DNA sequences formed four distinct clusters as expected, with 99-100% bootstrap support (Figure 1). Three of the four clusters were found in the previous study [10], while one cluster seen in the previous study, B, was absent from the present study. In accordance with the established nomenclature system for Cryptosporidium subtype families [11], the four clusters found in the present study were named as XIXa, XIXc, XIXd and XIXe (newly identified in the present study) subtype families, while the previous Cluster B was named as XIXb subtype family.…”
Section: Phylogenetic Relationship Among C Felis Subtypescontrasting
confidence: 69%
“…Among them, C. felis was initially reported in domestic cats from Japan in 1979 and proposed as a new species based on host occurrence and oocyst morphology, which was later supported by genetic characterizations of isolates [6,7]. This species has been reported in numerous human cases subsequently [8], and sometimes in association with the presence of infection in cats in the same household [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence difference is probably responsible for the failure of PCR to amply the gp60 locus in C. ryanae using the universal primers designed based on the sequences of C. parvum and C. hominis [21]. Unlike the gp60 gene of C. parvum and other closely related species/genotypes, the TCA/TCG/TCT repeats, which encode a polyserine tract and are used in differentiating subtypes within subtype families, are absent in the gp60 gene of C. ryanae, C. ubiquitum, and C. felis [5,10,23]. In C. ryanae, there is a polyglycine tract encoded by GTT repeats in this region of the gp60 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The application of gp60 subtyping tools has contributed greatly to our understanding of the genetic diversity, transmission dynamics, as well as host adaption in human-pathogenic Cryptosporidium spp. [5][6][7][8][9][10][11]. There is also a subtyping tool for C. andersoni based on sequence analysis of several genetic loci with simple tandem repeats [12].…”
Section: Introductionmentioning
confidence: 99%